Carney complex: a clinicopathologic and molecular biological study of a sporadic case, including extracutaneous and cutaneous lesions and a novel mutation of the PRKAR1A gene - Kacerovska, Denisa; Sima, Radek; Michal, Michal; Hes, Ondrej; Roucka, Patrik; Zarybnicka, Marta; Hora, Milan; Chudacek, Zdenek; Kazakov, Dmitry V (Journal of the American Academy of Dermatology, 2009)
BACKGROUND: Carney complex (CNC) is an autosomal dominant disorder associated with multiple neoplasms. OBJECTIVE: We report a case of a 40-year-old Caucasian man with a sporadic form of CNC. METHODS: This is a clinicopathologic description and molecular biological study with an emphasis on histopathologic findings. RESULTS: The patient presented with multiple cutaneous myxomas, cardiac myxomas, and spotty pigmentation at typical sites. Additionally, a blue nevus, a lipoma, multiple calcifications in both testes, and hypoechogenic areas suspected of being adenomas in the thyroid gland were found. Microscopically, the 2 cardiac and 6 cutaneous myxomas studied manifested a typical appearance, being composed of scattered polygonal, stellate, plump and/or spindle cells in a mucinous matrix containing small, sometimes dilated blood vessels. Of the 6 cutaneous myxomas, only in one lesion was there an abnormal epithelial component (tiny basaloid buds and a horn cyst). Molecular biologic study revealed a heterozygous shift mutation c.796dupA in exon 10 of the PRKAR1A gene. Physical examination and genetic testing of family members (both parents and two brothers) for the PRKAR1A mutation were negative, as was analysis of the peripheral blood of 110 randomly selected, unrelated healthy individuals for the above mutation. These findings suggest sporadic disease and a novel mutation in our patient. LIMITATIONS: None. CONCLUSION: Herein we report a case of sporadic CNC in which a novel mutation in PRKAR1A was identified.
Keywords: mužské pohlaví; Male; Humans; myxom; nádory srdce; lidé; nádory endokrinních žláz; Skin Neoplasms; Endocrine Gland Neoplasms; mladiství; Myxoma; Adolescent; syndrom; Cyclic AMP-Dependent Protein Kinase RIalpha Subunit; Syndrome; dospělí; Adult; Pigmentation Disorders; Heart Neoplasms; poruchy pigmentace; nádory kůže; proteinkinasy závislé na cyklickém AMP, podjednotka RIalfa